Studying the Solubility, Availability, and Uptake of Silicon (Si) from Some Ore Minerals in Sandy Soil - Rama T. Rashad; Rashad A. Hussien (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2018)
The solubility and availability of Si from the feldspar, silica, and zeolite as Si-bearing minerals were studied in a sandy soil. Silicon uptake by the soybean (Glycine max L.) plant was discussed. The minerals used were applied before planting in two separate rates; rate 1 ≈ 595.2 and rate 2 ≈ 1190.5 kg ha-1 accompanied by a ≈ 4.8 kg ha-1 constant rate of the K-humate sprayed as a solution on soil after planting in a complete randomized block design. The dissolved Si from the different minerals at rate 2 followed an opposite direction to their SiO2 percentage that may be due to the structural differences: silica (1.46 mg kg-1 - SiO2 =98.4%) < zeolite (1.71 mg kg-1 - SiO2 =75.9%) < feldspar (2.09 mg kg-1 - SiO2 = 71.9%). The individual mineral treatments at rate 2 have almost decreased the available NPK estimated after soybean harvesting. The K-humate has enhanced the effect of silica at rate 2 for the available N and P. The soybean seed yield (kg ha-1) increased significantly by 117.9% for the S1 + H, 109.2% for K-humate and 57.5% for the Z2 + H. The seeds’ Si (mg kg-1) increased significantly from 3.6% to 102.9% affected by the silica treatments.